"Leaps of faith": parents' and professionals' viewpoints on preparing adolescents on the autism spectrum for leaving school. Issue 3 (17th January 2017) - Hatfield, Megan; Falkmer, Marita; Falkmer, Torbjorn; Ciccarelli, Marina
Abstract : Adolescents on the autism spectrum experience difficulty transitioning from secondary school to post‐school activities, often due to transition planning processes that do not meet their unique needs. This study identified parents' and professionals' viewpoints on transition planning for adolescents on the autism spectrum. Interviews were completed with nine parents of adolescents on the autism spectrum and four professionals who worked with adolescents on the autism spectrum. A constant comparison approach was used to analyse the transcripts. Four themes were identified, reflecting parents' and professionals' viewpoints on how to meet the transition planning needs of adolescents on the autism spectrum. Supporting adolescents to grasp the big picture can enhance motivation to participate in transition planning. Autism can be an 'invisible disability'; therefore, encouraging adolescents to be active participants and to be seen in transition planning ensures their individual needs are met. Encouraging adolescents to have high aspirations in transition planning develops their self‐determination. Finally, to be prepared for the transition from school may reduce the adolescent's' anxiety. Adolescents on the autism spectrum face unique challenges in transition planning. The themes identified in this study provide insight into how parents and professionals might support adolescents with these challenges.